Understanding sustainability effectiveness on design strategy of ten-lane expressway merging areas based on entropy method - Yang, Hang; Liu, Yutong; Pan, Binghong; Ren, Xueyuan; Zhang, Jiale; Yan, Huang (Frontiers in Energy Research, 2023)
Due to the rapid growth of traffic volume, some existing expressways are being transformed into two-way ten-lane configurations. The increased lane flexibility of two-way ten-lane expressways implies a more serious mixing of passenger and freight traffic, thus necessitating a focus on traffic organization, especially at bottleneck sections. This study, based on field-measured data and traffic simulation, investigates the traffic applicability of five expressway entrance forms: conventional interchange entrance ramp (CI), passenger vehicles and trucks separation (PVTS), lanes separation around interchange (LSI), both left-side and right-side entrance ramp (LRER) and the stacked composite cross-section expressway (CCE). Using a comprehensive evaluation method, it provides optimal design solutions for varying traffic volumes, truck ratios, and merging ratios. Comprehensive evaluation results indicate that for one-way total traffic volumes exceeding 9,000 veh/h and truck ratios above 25%, the PVTS form should be prioritized. The LSI scheme demonstrates significant advantages when the truck proportion is below 30% and the merging ratio is above 20%. Additionally, due to its relatively low construction cost, it can serve as a good substitute for the PVTS approach. The LRER plan is unsuitable for entrance sections due to poor traffic capacity, increased CO emissions, and foreseeable safety issues. The strengths and applicability of PVTS, LSI, and CCE can guide the choice of entrance forms for ten-lane expressways.